Fire Phoenix facilitates phytoremediation of PAH-Cd co-contaminated soil through promotion of beneficial rhizosphere bacterial communities. (March 2020) - Dai, Yuanyuan; Liu, Rui; Zhou, Yuemei; Li, Na; Hou, Liqun; Ma, Qiang; Gao, Bin
Graphical abstract: Highlights: At 150 days planting, 64.57% ∑4PAHs and 40.93% Cd were removed in low-PAHs-Cd soil. PPO activities had a significant negative relation with ∑4PAHs removal rate. DHO was strongly associated with ∑4PAHs and Cd removal rates in low-PAHs-Cd soil. The removal rate of Cd had a significant positive relation with ∑4PAHs removal rate. Four dominant genera promoted, related to high PAH and Cd removal rate by Fire Phoenix. Abstract: Pot experiments were conducted in a growth chamber to evaluate the phytoremediation efficiency and rhizosphere regulation mechanism of Fire Phoenix (a mixture of Festuca L.) in polycyclic aromatic hydrocarbon-cadmium (PAH-Cd) co-contaminated soils. Plant biomass, removal rates of PAHs and Cd, soil enzyme activity, and soil bacterial community were determined. After 150 days of planting, the removal rates of the total 4 PAHs and Cd reached 64.57% and 40.93% in co-contaminated soils with low-PAH (104.79–144.87 mg·kg −1 ), and 68.29% and 25.40% in co-contaminated soils with high-PAH (169.17–197.44 mg·kg −1 ), respectively. The polyphenol oxidase (PPO) activity decreased in soils having Fire Phoenix, while the dehydrogenase (DHO) activity increased as the changes of DHO activity had a strong positive correlation with the removal rates of PAHs and Cd in the low-PAH soils (r = 0.862 ( P  < 0.006) and 0.913 ( P  < 0.002), respectively). Meanwhile, successional changes in the bacterial communities were detected using high-throughput 454 Gs-FLX pyrosequencing of the 16S rRNA, and these changes were especially apparent for the co-contaminated soils with the low PAH concentration. The Fire Phoenix could promote the growth of Mycobacterium, Dokdonella, Gordonia and Kaistobacter, which played important roles in PAHs degradation or Cd dissipation. These results indicated that Fire Phoenix could effectively motivate the soil enzyme and bacterial community and enhance the potential for phytoremediation of PAH-Cd co-contaminated soils.